Associations between meeting 24h movement behavior guidelines and cognition, gray matter volume, and academic performance in children and adolescents: a systematic review - Bo Liu; Peng Shi; Teng Jin; Xiaosu Feng (Archives of Public Health)
Abstract Background 24-h movement behaviors have a close relationship with children and adolescents' cognition, gray matter volume, and academic performance. This systematic review aims to precisely explore the associations between meeting different combinations of guidelines and the aforementioned indicators, in order to better serve public health policy. Methods Computer retrieval was conducted on CNKI, Web of Science, PubMed, SPORT Discus and Cochrane library databases. The screening and data extraction processes were conducted by two researchers. This study used the Joanna Briggs Institute checklist for methodological quality assessment and the Grading of Recommendations Assessment, Development, and Evaluation system for the evaluation of the level of evidence. Descriptive statistical analysis is performed using frequency and percentage on the extracted data and key findings, primarily to assess the consistency of the positive benefits associated with meeting different guidelines and outcome variables. Results A total of 10 studies were included (with 16 correlation analyses conducted), involving 51,566 children and adolescents aged between 4.2 and 15.9 years old. The included studies generally agreed upon the following associations: adherence to the screen time (ST) guidelines is positively linked to fluid intelligence; adherence to the sleep duration (SD) guidelines is positively linked to literacy; adherence to both ST and SD guidelines is associated with increased fluid intelligence and gray matter volume; and overall adherence to all guidelines is positively correlated with fluid intelligence. The included studies reported low certainty of evidence. Additionally, the included studies have provided clear evidence, but some studies did not strictly control confounding factors, and it is also unclear whether there is a larger effect size, hence the level of evidence is relatively low. Conclusion There are varying degrees of associations between different combinations of guidelines and cognition, gray matter volume, and academic performance, but further research is needed to confirm these findings, especially the relatively limited role of meeting physical activity guidelines.